TECHNOLOGICAL ASPECT OF IDENTIFYING AND OVERCOMING THE CAUSES OF STUDENT FAILURE AND TAKING INTO ACCOUNT THE INDIVIDUAL APPROACH IN LEARNING - Kozachenko, I.A. (Pedagogy of Higher and Secondary Education, 2009)
No abstract.